Harmonious Co-Existence between Nature and Mankind: An Investigation of a Satoyama Development – Like Mechanism at Imbak Canyon Conservation Area (ICCA), Sabah - Tracy Angki; Robert Francis Peters; Nordiana Mohd Nordin; Fiffy Hanisdah Saikim (2020)
This research is a preliminary survey of Satoyama development-like mechanism in Kg. Imbak, Tongod, Sabah. The objectives of this research are to determine the utilization of forest source among the local community in Kg. Imbak and their community-based conservation efforts. Face to face interviews were conducted to access primary data besides observation surveys. The data gathered are from published materials such as reports and articles. Kg. Imbak consists of Dusun Sungai People with a total population of 796 people. Collected data were analyzed using Descriptive Analysis and SWOT analysis. Kg Imbak is approximately 19.12 km drive from Tongod District and the local community still consumes forest source for their medicinal needs, bush meat, handicraft and construction materials such as using Ironwood tree to make coffins. Based on data collected, the Internal Factor Estimate Matrix (IFEM) is 2.59 while the External Factor Estimate Matrix (EFEM) shows a total of 2.58 indicating that Kg. Imbak, Tongod has a great potential and opportunities in terms of practicing the Satoyama model. There are 52 strategies determined in this research by using pair wise matching SO, WO, ST and WT.